Specific Induction of Double Negative B Cells During Protective and Pathogenic Immune Responses - Ruschil, Christoph; Gabernet, Gisela; Lepennetier, Gildas; Heumos, Simon; Kaminski, Miriam; Hracsko, Zsuzsanna; Irmler, Martin; Beckers, Johannes; Ziemann, Ulf; Nahnsen, Sven; Owens, Gregory P.; Bennett, Jeffrey L.; et al. (Frontiers in Immunology, 2020)
Double negative (DN) (CD19+CD20lowCD27-IgD-) B cells are expanded in patients with autoimmune and infectious diseases; however their role in the humoral immune response remains unclear. Using systematic flow cytometric analyses of peripheral blood B cell subsets, we observed an inflated DN B cell population in patients with variety of active inflammatory conditions: myasthenia gravis, Guillain-Barré syndrome, neuromyelitis optica spectrum disorder, meningitis/encephalitis, and rheumatic disorders. Furthermore, we were able to induce DN B cells in healthy subjects following vaccination against influenza and tick borne encephalitis virus. Transcriptome analysis revealed a gene expression profile in DN B cells that clustered with naïve B cells, memory B cells, and plasmablasts. Immunoglobulin VH transcriptome sequencing and analysis of recombinant antibodies revealed clonal expansion of DN B cells that were targeted against the vaccine antigen. Our study suggests that DN B cells are expanded in multiple inflammatory neurologic diseases and represent an inducible B cell population that responds to antigenic stimulation, possibly through an extra-follicular maturation pathway.